Penerapan Model Pembelajaran Quantum Teaching untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa Sekolah Dasar - Andrian, Firma (Research in the Mathematical and Natural Sciences, 2022)
The purpose of this study was to determine the increase in student activity and learning outcomes in mathematics subjects after applying the Quantum Teaching. The research method used in this research is Classroom Action Research. The data collection technique used is observation to observe student learning activities while to see the increase in learning outcomes using tests. The data analysis technique used is qualitative data analysis and quantitative data analysis. Qualitative data analysis techniques were used to analyze student learning activities during the learning process. While the quantitative data analysis technique was used to analyze the score acquisition of the student learning activity observation sheet and student learning test results by calculating the average acquisition of each cycle. The results showed that the application of the Quantum Teaching provided an increase in student activity and learning outcomes. Learning activity in cycle 1 was 63.99% which then increased in cycle 2 by 79.35%. As for student learning outcomes in cycle 1 and cycle 2 of 100%.